Hungary's crisis of democracy : the road to serfdom - Wilkin, Peter, 1963- (Lexington Books, 2016)
This book examines the crisis of democracy in Hungary since the election of the Fidesz government in 2010. It argues that Fidesz seeks to challenge the capitalist and democratic transformation that shaped Hungary after the fall of communism by increasing the power of the state over crucial aspects of the economy, society, and the political system.